GOOD AND EVIL AS VECTORS OF FREE WILL IN THE STRUCTURE OF ANTHROPIC TIME - V. B. Khanzhy; D. M. Lyashenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The work is aimed at comprehending good and evil as vectors of free will in the structure of anthropic time. Methodology. The study is based on: 1) the general theory of systems (A. I. Uyomov, A. Yu. Tsofnas, L. N. Terentyeva) – while justifying the possibility of representing the anthropic time as a system in general; 2) synergetics – while considering the anthropic time as a complex self-organizing system; 3) the concept of «а whole in a whole» (I. V. Yershova-Babenko) – while identifying the optimal principle of correlation of the time units, taking into attention their ethical multi-vectority. Originality. In the context of the reconstruction of the concept of anthropic time: 1) the authors revealed ethical vectors of expansion of free will as the driving principle of human temporality (the vectors of «freedom for good» and «freedom for evil»); 2) the authors justified the optimality of using the principle of complementarity in solving the problem of harmonizing the coexistence of units of anthropic time («matryoshkas of time»). Conclusion. 1) In a line with the tradition of anthropologization of the problem of good and evil, these intentions of human activity are interpreted as vectors of free will in the structure of anthropic time; 2) the paper represented anthropic time as a system in general (based on the general theory of systems) and as a complex self-organizing system in particular (based on a synergetic methodology); 3) constituting of the system of anthropic time by the existential-actionable concept allowed to overcome the position of the one-vectored time, i.e.to reveal the ethical binarity of the anthropic time vectors prepared by the duality of expansion of free will as its driving principle; 4) formulation of the problem of discrepancy between the intentions of different temporal systems showed the optimality of the complementarity principle in solving the question how to harmonize the relations of anthropic time units; 5) the conducted research opens prospects for consideration of external determinants of anthropic time, as well as for search of variants of their correlation with the internal mover (free will) in the structure of human temporality.